THE INFLUENCE OF ENVIRONMENTAL FACTORS ON THE ORGANISM DEPENDING ON AGE - Qudratova Gulnoza Ulug'bek qizi; Arsenova Muhabbat Abdumo'minovna (American Journals Publishing, 2024)
This paper explores the complex relationships between environmental factors and age-related health outcomes by examining how different stages of life affect susceptibility to environmental risks. Factors such as environmental pollution, climate changeability and lifestyle choices can have a significant impact on the human body, which can have different effects depending on age. By analysing the correlation between environmental exposure and age-related changes in physiology and vulnerability to disease, this study aims to fully understand how individuals at different stages of life are exposed to the environment.
Keywords: Nature, Environment, Diseases, Environmental Factors, H Arorat.